Constructing tunnels to troubleshoot complete pleural symphysis during video-assisted thoracic surgery - Liu, Chengwu; Pu, Qiang; Liao, Hu; Ma, Lin; Mei, Jiandong; Lin, Feng; Guo, Chenglin; Liu, Lunxu (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
Background: Pleural symphysis (PS) is once considered a relative contraindication of video-assisted thoracic surgery (VATS). This paper aims to present our experiences in troubleshooting complete PS during VATS by constructing tunnels in the pleural space and to discuss the indication of thoracoscopic adhesiolysis in cases with complete PS. Methods: A total of 1163 consecutive VATS major lung resections were performed between May 2006 and July 2013. Among these, 17 cases were identified with complete PS. Blunt adhesiolysis using a finger was attempted around the three incisions to initiate accesses to the pleural space. Then communication between the observation incision and the two utility incisions was accomplished by constructing tunnels. Further adhesiolysis was performed with alternating blunt dissection and electrocoagulation through the two constructed tunnels. Detailed information on the patients was carefully reviewed. Results: Three cases underwent conversion to thoracotomy because the pleural space cannot be accessed due to dense PS. Fourteen cases with complete PS underwent successful thoracoscopic adhesiolysis. The median operation time was 150 min, ranging from 120 to 210 min. The median blood loss was 125 mL, ranging from 50 to 700 mL. The median chest drainage was 725 mL, ranging from 400 to 2,000 mL. The median chest drainage duration was 4 days, ranging from 2 to 12 days. Four patients incurred postoperative complications (two cases of pneumonia and two cases of prolonged air leakage), and all of them were treated appropriately. The median length of postoperative hospital stay was 6.5 days, ranging from 4 days to 18 days. Perioperative mortality was not observed. Conclusions: This method is a novel approach to troubleshoot complete PS via VATS. The successful tunnel construction in the pleural space indicates further thoracoscopic adhesiolysis in cases with complete PS.